(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
This article presents the theoretical approaches, pedagogical terms and practical ways to the organization and prevention of myopia in primary schoolers. It is commonly known, that myopia is often observed at school age, when a child does not follow the rules, regulations, and requirements set for the protection of vision and visual work during games, drawing, viewing pictures and drawings, computer activities, etc. This determines the necessity of versatile and deep studying of this issue and developing of theoretical approaches, pedagogical terms and practical ways for prevention of myopia in primary schoolers. The literary data and work experience indicate that the role of the school is immeasurably increasing in the general system of a child development, in strengthening the health of pupils, shaping the personality and preventing myopia. Unfortunately, may teachers do not pay needed attention to the conditions of conducting the child’s visual work, and often do not have the necessary information about the rules and standards of visual work and rest of the child’s eyes. Therefore, the study of many aspects of this problem and the development of theoretical approaches, pedagogical terms and practical ways for the organization and prevention of myopia in primary schoolers will be the basis for a successful solution of this problem and maintaining good vision in children.